2022
DOI: 10.1177/00332941221144605
|View full text |Cite
|
Sign up to set email alerts
|

Self-Other Balance in Context: A Quiet Ego May Be Meaningful and Adaptive in Latinx/Hispanic Cultures and Work Settings

Abstract: Quiet ego is a relatively novel, increasingly studied, multi-dimensional concept characterized by a compassionate, interdependent worldview and an adaptive balance between self-interest and concern for others. Quiet ego has been associated with a range of characteristics that can promote relationship quality, responding effectively in the face of challenges, and greater well-being. However, it is currently unknown to what extent quiet ego translates across cultures and settings. The present research leverages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
2
0
0
Order By: Relevance
“…In the present study the Quiet Ego was positively related to self-esteem, psychological wellbeing, subjective happiness, resilience, supporting prior studies (Wayment et al, 2015a ; Akca and Sumer, 2016 ; Watson, 2018 ; Bistricky et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study the Quiet Ego was positively related to self-esteem, psychological wellbeing, subjective happiness, resilience, supporting prior studies (Wayment et al, 2015a ; Akca and Sumer, 2016 ; Watson, 2018 ; Bistricky et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study the Quiet Ego was positively related to selfesteem, psychological wellbeing, subjective happiness, resilience, supporting prior studies (Wayment et al, 2015a;Akca and Sumer, 2016;Watson, 2018;Bistricky et al, 2022). A recent study of suggested, in fact, the possibility of ameliorating self-regulatory abilities through a therapeutic approach based on the quiet ego to better manage stressful situations.…”
Section: Discussionsupporting
confidence: 89%